Nonexecutive Directors at Early-Stage Startups - Venugopal, Buvaneshwaran; Yerramilli, Vijay (The Review of Corporate Finance Studies, 2025)
Abstract Most non-executive-directors appointed by early-stage startups are not investors in the startup, and only a small fraction are venture capital (VC) directors. Non-investor-directors and angel directors are more likely to be appointed when they possess experiences that founders lack and leverage their professional connections to attract new investors, directors, top executives, and potential acquirers for startups. Among early-stage startups that appoint nonexecutive directors, those with investor-directors experience better later-stage funding outcomes and a higher likelihood of exit, as well as file fewer patents and are more likely to exit via acquisitions rather than IPOs compared to similar startups with non-investor-directors. (JEL G24, G34, L26, M13)